Tata Kelola Perusahaan, Etika Bisnis, dan Kepuasan Karyawan dalam Pengelolaan Lembur Outsourcing Sesuai Regulasi Ketenagakerjaan: Studi Kasus PT. Bantu Bantu Selaras - Vera Salma Meilania; Agus Satory (MANAJEMEN, 2026)
This study examines the relationship between corporate governance, business ethics, and employee satisfaction, and how these factors influence the management of overtime among outsourced employees at PT Bantu Bantu Selaras in compliance with Indonesian labor regulations. A quantitative approach was employed using a questionnaire survey administered to 53 outsourced employees. The study evaluates the effectiveness of transparent and accountable governance and ethical practices by applying the Community Satisfaction Index (CSI) and Importance–Performance Analysis (IPA) techniques. The results indicate that corporate governance and business ethics are implemented at a very high level, as reflected in satisfaction scores exceeding 4.6 out of 5 in key areas such as transparency, social security (BPJS), and compensation. However, the frequency of overtime remains an aspect that requires better management to prevent employee fatigue and potential long-term risks. Overall, the findings contribute to the development of fair, ethical, and legally compliant human resource management practices within the Indonesian outsourcing sector.